The Effect Of Leadership, Discipline, and Motivation on Teacher and Staff Performance at MI Al Bukhori Surabaya - Karimul Ahlaq; Hafidulloh Hafidulloh; Gogi Kurniawan; Dani Rohmati (Improvement: Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of democratic leadership style, work discipline, and work motivation on the performance of teachers and educational staff at MI Al Bukhori Surabaya. This research employs a quantitative approach with a saturated sampling technique involving 35 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 25. The results indicate that partially, democratic leadership style, work discipline, and work motivation have positive but insignificant effects on performance. However, simultaneously, these variables significantly influence performance. The coefficient of determination (R²) of 0.377 shows that 37.7% of performance variation is explained by the model, while 62.3% is influenced by other factors. Work motivation is the most dominant variable with a standardized beta value of 0.366, although it is not statistically significant. Keywords: democratic leadership, work discipline, work motivation, performance, education